A aceleração dos ciclos da moda - Mitre, Maria Augusta da Silveira (2016)
This study focuses on the fashion transformations in contemporary times, and more specifically on the fashion cycles. In particular, it assess the hypothesis that the cycles are shortened to the extreme and are no longer closing, establishing a coexistence of styles. Based on the thought of Gilles Lipovetsky, this study also shows that the classical concept of fashion no longer covers all the settings that comprise the modern phenomenon. The choice of this author is due to the greater complexity of his ideas compared to previous theories, and in particular, because of his vision of fashion. This study also draws from the classic reflections of Walter Benjamin on the relationship between fashion and cultural industry in modernity, which is also based on the idea of transience. The concepts of "urban tribes" and “supermarket of style " by Ted Polhemus are also employed. The corpus of this work is embodied in seven panels composed by a selection of Vogue America covers along six decades, from 1950 to 2000. The magazine was chosen because it is a widely distributed vehicle both in the country of origin, the United States, center of contemporary fashion, as in the rest of the world, with regionalized versions, which are available on the Vogue Archive since its first edition in the year of 1892. The documentation provided by Vogue America enables the empirical identification of the main features of contemporary fashion and of its cycles. The methodology is bibliographical and documentary research